TRAINING OF 3D LEARNING MEDIA CREATION TO IMPROVE SPATIAL ABILITY IN GEOMETRY - Nurhidayati, Rina; Prasasty, Aliffia Teja; Isroyati, Isroyati (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
The training on making 3D learning media for geometry spatial material aims to improve teachers' skills in developing and using interactive learning media that can visualize mathematical concepts more clearly and attractively. The target of this training is 10 mathematics teachers at the Nurul Aini Foundation. The time of this research is October 21, 2024. The stages in this activity are, analysis of partner problems, preparation, implementation and evaluation. At the implementation stage, teachers are given the opportunity to design 3D objects on spatial geometry materials. At the evaluation stage, participants are given a posttest to see the extent of the participants' abilities after the training and to see how the participants assess the training activities. The results of this activity show that participants gain new skills to create 3D media that can be used in mathematics learning to improve student understanding and participants give a positive response to this training activity.